The Effect of Using Quizizz on Students’ Learning Motivation in MAN 2 Samarinda - Rahman, Muhammad Rezza Nur; Riyadi, Ahmad; Darwis, Darwis; Musfiroh, Imroh Atul (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2024)
A B S T R A C T Surveys conducted by researchers stated that 63.1% of the 130 students of class XI Regular in MAN 2 Samarinda felt that learning Al-Qur'an Hadith was boring. This research was conducted to determine the magnitude of effect using Quizizz on students’ learning motivation in the subject Al-Qur’an Hadith in MAN 2 Samarinda. This research uses quantitative type with pre-experimental approach and one group pretest-posttest design. Sample was selected by simple purposive sampling techniques with some criteria and obtained 32 students at XI IPS 1 as a sample. To collected data, researchers used questionnaire on students’ learning motivation in the subject Al-Qur’an Hadith. Data analysis using non-parametric statistic with Wilcoxon, supported with SPSS version 20 Program. The result showed Asymptotic Significance level was 0,00 < 0,05, which means there was effect using Quizizz on students’ learning motivation. Descriptive analysis showed average increase 21% generated from the difference average pretest and posttest data.